Cuidados em saúde às mulheres em situação de rua: estratégias, serviços e cuidados na realidade brasileira. - Dionisio, Bianca Waylla Ribeiro (2021)
The ritualization process is a historical, multicausal phenomenon, which is characterized as the movement of subjects that make the street their home and/or workplace. Regarding gender, there is a predominance of males, both in national and state data, although there is a significant number of women living in conditions of extreme vulnerability resulting from the street situation, which are enhanced when crossed by issues related to race and class. Therefore, the objective of this research was to analyze, from the feminist epistemology and Foucauldian theory, the strategies of health care directed to women in the context of street situation in Brazil. An integrative review with qualitative meta-synthesis based on international protocols was used for its execution. The bibliographical search was carried out in six databases using MeSH, DeCS and keywords. A total of 7,433 studies were identified. After screening, 203 were fully evaluated, resulting in 24 articles included in English, Portuguese and/or Spanish. The results outlined the numerous violence experienced by women living on the streets in Brazil, from those uttered by intimate partners and even reproduced in health services, i.e., the institutional violence. The findings state that institutional or structural violence significantly impairs the search for care due to stigmatization, discrimination and social exclusion. The low effectiveness and efficiency of the predominant medical intervention model is notorious. Thus, there is extreme need for research and policy interventions in health that address and understand the issues of gender, race and class in the care of the street population, especially in health policies already in place.